MESIN PENUMBUK MELINJO SISTEM ALU VERTIKAL UNTUK PEMBUATAN EMPING KAPASITAS 30 KG/JAM - Gultom, D; Oppusunggu, K; Nurdiana, Nurdiana; Mahyunis, Mahyunis; Supriadi, Supriadi (MEKANIK: Jurnal Ilmiah Teknik Mesin, 2019)
In this design a melinjo pounding machine is made with a capacity of 30 kg / hour with a vertical pestle. The mechanism for melinjo collision is to put melinjo into the funnel provided, then the collector will pound the melinjo that has been inserted. 3 pulleys were used with nominal diameters of 7 inches, 8 inches and 8 inches, belts with 49 inches long belts, 2 gears with 6 inches diameter, 1 conveyor belt with 94 cm lengths and 3 inches wide, pulverizer rods with 25 cm length and diameter of 40 mm, with a frame height of 95 cm, width 42 cm. Shaft material is made of S35C with a tensile strength of 53 kg / mm2, shear stress clearance (τa) shaft material, (τa) = 4,417 (kg / mm2), twisting or torque occurring, T = 519 (kg.mm), diameter permitted shaft = 16 (mm), shaft diameter used in bearings = 20 (mm), Twisting angle that occurs, θ = 0.0471 (°), the shaft is declared safe because the shaft used for the defect is smaller than the provisions which have been set . (0.0471 °